The lived experience of students with visual impairment from living with sighted mothers: A qualitative study - Khonsari , Fatemeh; Ashori , Mohammad (Applied Family Therapy Journal (AFTJ), 2023)
Aim: Visual impairment is one of the problems that make the interaction of a child with visual impairment with family members, especially the mother. The purpose of the present study was the phenomenology of the lived experience of students with visual impairment from living with sighted mothers. Method: The approach of this research was qualitative and based on the phenomenological method. The research population included all students with visual impairment and sighted mothers in Isfahan province in the academic year of 2021-2022, of which 14 were selected using a purposive sampling method. In-depth and semi-structured interviews were used to collect data. The interviews were recorded and transcribed verbatim and analyzed using the seven-steps Claisen method. Results: In this study, 7 main categories including acceptance of the child by the parents, acceptance of the parents by the child, independent life, leisure time, affections and emotions, education and learning, and orientation and mobility, and also 19 subcategories were extracted. The main categories included acceptance of the child by the parents, acceptance of the parents by the child, independent living, leisure time, emotions and emotions, education and learning, and orientation and movement. Conclusion: Based on the findings of this study, factors such as acceptance, independence, leisure, emotion, education and movement skills of students with visual impairment are very importance and have a positive impact on their quality of life. As a result, implementing appropriate educational programs based on the extracted categories for this group of students and their parents can help improve their interaction